The Effectiveness of Storytelling in Developing Children’s Social Care Character through Descriptive Literature Review - Kusniasari, Sofiani; Kosasih, Aceng; Hakam, Kama Abdul; Rakhmat, Cece (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
The decline in children’s social care character has become increasingly evident in recent years, marked by reduced empathy, rising individualism, and the weakening of prosocial behaviors within the school environment. This condition necessitates the development of pedagogical strategies capable of meaningfully fostering the value of social concern. This article aims to describe the effectiveness of storytelling in developing social care character through a descriptive literature review. The method employed is a literature review of national and international articles relevant to character education, storytelling, teacher and child dialogic interaction, and children’s social development. The findings reveal that storytelling contributes to improving children’s ability to understand others’ perspectives, internalize moral values, and demonstrate social care behaviors such as sharing, cooperating, and helping peers. The dialogic approach in the storytelling process also strengthens children’s emotional engagement, thereby facilitating the internalization of character values. Overall, this literature review confirms that storytelling is an effective, easily adaptable instructional strategy that can be integrated across various fields of knowledge to strengthen character education from an early age.